(untitled) (Polis (Santiago), 2019)
This research explores alternatives to the forms of land management built by Mapuche communities south of Villarrica National Park (PNV). Like other conservation units, the establishment of the PNV implied making ancestral practices invisible and distancing them from the material and symbolic wealth present in the territory. Before the policies of the dominant development model that places its interest in the tourist potential, in the goods and in the ecosystem services present in the zone, the content that the communities give to this area from their own capacities becomes relevant, looking for an alternative type of development that facilitates experiencing self-determination and facing impoverishment. We conclude that the territorial re-appropriation of the PNV is fundamental to overcome immaterial poverty and that the communities have their own tools to manage the territory autonomously and synergetically.